Methods of Using Geographic Information Systems (GIS) to Detect Underground Water Reservoirs in Babil Governorate, Data and Mathematics for the Year 2020 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Depending on the application of hydrological analysis steps in the geographic information systems (GIS 10.4) program from the graph (graph). This study was carried out to determine The Areas for groundwater gathering in Babil Governorate. the research was prepared from 1/1/2020 Until 11/15/2020. Likewise, The research relied on an accurate mechanism in Analyzing the study spatial data and linking it to the metadata of the study in geographic Information systems, which helped in studying the newspaper, the newspaper, the Newspaper, for groundwater Reservoirs in the database Good and advanced data building. The volume of the first reservoir (Hashemite) is 2746459408 m3, the ground level is 6 m, the depth of wells is (11-12) meters, the reservoir and the level of groundwater, the volume of The second tank (Hilla district) is 4211330480 m3, the water level is 2.5 m and the depth of The wells is (8.-12) meters, The Volume of the tank, the depth of the third (transformers) 1378751024 m3, the water level is 2.5 m, the depth of the wells of the reservoir is 12 meters, the fourth tank (al-Kifl) is 611683856 m3, the water level is 2 m, the depth of wells in the reservoir is (9-14) meters, the volume of the fifth tank (al-Musayyib) ) 1449446656 m 3, the Groundwater level is 3 meters, and the depth of the Wells of the reservoir is (10-12) meters. As for the sixth reservoir (Al-Musayyib dam), its Volume reached 1,308,618,304 m3, the Water level is 3 meters, and the depth of the wells of the Reservoir is (8-12) meters, the size of the seventh reservoir (Al-Shomali) 1711325392 m3, the water level is 6 m, the depth of the wells of the reservoir is (11-12.5) meters, the volume of the eighth tank (the Imam side) Is 499369584 m, the groundwater level is 3 meters, the depth of the Wells of the reservoir is (8-12) meters, the volume of the ninth reservoir (Abi Gharaq The water level is 117596080 m3, the water level is 3 m, and the depth of the wells of the reservoir is (9-12) m. The total volume of the (nine) groundwater reservoirs reached the study 14034580784 m 3.